Stratigraphy and mineralogy of tailings at Macraes gold mine, southern New Zealand. Issue 3 (3rd July 2022) - Weightman, Erin; Craw, Dave; Snow, Tom; Christenson, Hannah; Kerr, Gemma
ABSTRACT: Processed tailings in the Mixed tailings impoundment at the Macraes gold mine built up a sedimentary pile up to 100 m thick between 1990 and 2013. The tailings consist of sand-dominated fluvio-lacustrine sediments with fine (cm scale) bedding and have a mineralogical stratigraphy that reflects changing mine processes. Most of the tailings (>90%) consist of silicate minerals discarded from the flotation system throughout that time. The deepest tailings (1990–1993) have the lowest contents of sulphides as these were extracted and deposited separately. Between 1993 and 1999, tailings with up to 0.5 wt% sulphide sulphur (as pyrite and arsenopyrite) were deposited. Introduction of a pressure oxidation system in 1999 caused a substantial decrease in sulphide minerals and a parallel increase in ferric oxyhydroxide, ferric sulphate, and ferric arsenate compounds in which trace metals are dispersed. Some primary scheelite reacted during pressure oxidation conditions to form ferric tungstate compounds. Processing of auriferous sulphide concentrate from Reefton, western South Island, from 2007 introduced stibnite to the ore stream, and this was readily oxidised to form insoluble As-bearing ferric antimonate.